Lives Punctuated by War: Civilian Volunteers and Identity Formation Amidst the Donbas War in Ukraine - Stepaniuk, Nataliia (Université d'Ottawa / University of Ottawa, 2018)
This dissertation examines civilian mobilization amidst the Donbas war in Ukraine and the identity formation processes that it engendered. It focuses on ordinary residents of the frontline regions who voluntarily got together to address the humanitarian and military consequences of war in the absence of state support. It explores the micro-level dynamics of mobilization, particularly the demographic profile of volunteers, their motivations to join and their pathways to engagement. In so doing, it provides an account of how ordinary residents of seemingly passive regions became active in times of crisis. I use the concept of “identity formation” to analyze how war and war engagement have impacted citizen, gender, national and language identities of those active at the rear. The outbreak of war shattered habitual ways of thinking and acting and brought about new modes of belonging and meaning making for war volunteers. My findings suggest that successful volunteer efforts in wartime allowed volunteers to position themselves differently with respect to community, nation, and the state and to articulate new understandings of “good citizenship.” The shifting positioning of volunteers, as the research demonstrates, is inherently linked to the changing citizen regimes in Ukraine and the gendered conceptions of who counts as a legitimate member of the community. By employing ethnographic tools of inquiry, the dissertation provides an ethnographic account of wartime social change “from below” and speaks to larger social and political transformations in wartime using Ukraine as a case study. It does so with attention to the social-political environment within which collective action occurs and in relation to the new types of mobility, socializing and bonding it engenders.
Keywords: civilian mobilisation; wartime engagement; identity formation; war-affected communities; citizenship; gender identities; national identities; language identities; Ukraine; Donbas war